2010
DOI: 10.1111/j.1744-313x.2010.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of COL11A2 polymorphism with susceptibility to Kawasaki disease and development of coronary artery lesions

Abstract: Kawasaki disease (KD) is a pediatric systemic vasculitis of unknown etiology wherein genetic influence is suspected. Gene clusters within the HLA region at chromosome 6p21.3 have been linked to KD and other autoimmune disorders. As collagen is a strong autoantigen inducing chronic inflammation in patients with vasculitis, this study tests a hypothesis that single-nucleotide polymorphism (SNP) of a collagen gene, COL11A2, located in this HLA region may affect susceptibility to Kawasaki disease and its arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“… [18] Thus, type XI collagen could act as an autoantigen, leading to the production of autoantibodies, and in this patient, the conformational changes induced by the variants in the COL11A2 gene may have changed the immunogenicity of type XI collagen, leading to the production of autoantibodies and arthritis. In addition, variants in the COL11A2 gene have been reported to be associated with inflammatory disorders including Kawasaki disease, [19] suggesting that abnormalities in type XI collagen may cause deregulation of the immune system. Furthermore, it has been suggested that the risk of RA is increased in patients with osteoarthritis, presumably due to increased inflammatory cytokines and citrullinated proteins in the joints of osteoarthritis patients, [20] and osteoarthritis, caused by the variants in the COL11A2 gene, may also have contributed to the development of seropositive, inflammatory arthritis in this patient.…”
Section: Discussionmentioning
confidence: 99%
“… [18] Thus, type XI collagen could act as an autoantigen, leading to the production of autoantibodies, and in this patient, the conformational changes induced by the variants in the COL11A2 gene may have changed the immunogenicity of type XI collagen, leading to the production of autoantibodies and arthritis. In addition, variants in the COL11A2 gene have been reported to be associated with inflammatory disorders including Kawasaki disease, [19] suggesting that abnormalities in type XI collagen may cause deregulation of the immune system. Furthermore, it has been suggested that the risk of RA is increased in patients with osteoarthritis, presumably due to increased inflammatory cytokines and citrullinated proteins in the joints of osteoarthritis patients, [20] and osteoarthritis, caused by the variants in the COL11A2 gene, may also have contributed to the development of seropositive, inflammatory arthritis in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…DEFB1 [136], SLC11A1 [137], SPINK1 [138], CCR1 [139], GLUL (glutamate-ammonia ligase) [140], GPR84 [141], SIGLEC5 [142], SIGLEC7 [143], LGR5 [144], CD38 [145], GRB14 [146], PRDX1 [147], SLC19A2 [148], CADM2 [149], TRPM5 [150], COL1A1 [151], CTRB1 [152], UTS2R [153], CRTC1 [154], MUC5B [155], TMPRSS6 [156], SLC5A2 [157] and KCNJ9 [158] expression were shown to play an important role in diabetes mellitus, but these genes might be novel target for MI. MT1A [159], LYVE1 [160], S100A12 [161], GCKR (glucokinase regulator) [162], TLR8 [163], MRC1 [164], AGTR1 [165], P2RY12 [166], MSR1 [167], NQO1 [168], FKBP5 [169], CMTM5 [170], ADH1C [171], APLNR (apelin receptor) [172], SFRP4 [173], CCL3 [174], COL11A2 [175], EGR3 [176] and IL2RB [177] expression have a role in coronary artery disease. EDN2 [178], SNX10 [179] and KCNN1 [180] were played a predominant role in progression of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Çok nadirdir ve COL11A2 geninde mikrognati, glossopitozis, nonsendromik yarık damak, Kawasaki hastalığı, koroner arter lezyonları ve işitme azlığı gibi çok sayıda mutasyon ve polimorfizmler bildirilmiştir (2). Küçük burun ve nazal köprü basıklığı ile olan mid-fasiyal hipoplazi tipik yüz görüntüsüdür.…”
Section: Sayın Editör;unclassified